Proceedings of the 2017 on Workshop on Privacy in the Electronic Society 2017
DOI: 10.1145/3139550.3139555
|View full text |Cite
|
Sign up to set email alerts
|

Is Geo-Indistinguishability What You Are Looking for?

Abstract: Since its proposal in 2013, geo-indistinguishability has been consolidated as a formal notion of location privacy, generating a rich body of literature building on this idea. A problem with most of these follow-up works is that they blindly rely on geo-indistinguishability to provide location privacy, ignoring the numerical interpretation of this privacy guarantee. In this paper, we provide an alternative formulation of geo-indistinguishability as an adversary error, and use it to show that the privacy vs. uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…In this manner, the actual location of the user will never be sent to the LBS. [30] reported that for maintaining a high level of privacy in GeoInd the utility must be sacrificed. Thus, the information retrieved from LBS using GeoInd may not be useful unless users sacrifice some degree of privacy.…”
Section: Privacy Layermentioning
confidence: 99%
“…In this manner, the actual location of the user will never be sent to the LBS. [30] reported that for maintaining a high level of privacy in GeoInd the utility must be sacrificed. Thus, the information retrieved from LBS using GeoInd may not be useful unless users sacrifice some degree of privacy.…”
Section: Privacy Layermentioning
confidence: 99%
“…Differential privacy is guaranteed by adding noise, drawn from a two-dimensional Laplace distribution. Further version of Geo-I have been developed in [5] and [22].…”
Section: A Location Privacy Protection Mechanismsmentioning
confidence: 99%
“…Those works both introduce a model and a number of metrics to evaluate privacy and utility of LPPMs. Indeed, despite formal guarantees are needed in most contexts, they do not always translate well how an LPPM behaves in practice, as it has been shown in several works (e.g., [156], [157], [158]). On the privacy side, we advocate (similarly to, e.g., [124]) that metrics relying on adversary attacks should be considered as complimentary to the formal guarantees.…”
Section: A Quantifying Location Privacymentioning
confidence: 99%